KARAKTERISASI MOLEKULER PROTEIN FLAGELLIN Salmonella typhi ISOLAT JAWA TENGAH DAN YOGYAKARTA - Sri Darmawati; Budi Santosa; Ragil Saptaningtyas (Universitas Muhammadiyah Semarang, 2015)
The purpose of this study is to molecularly characterize 7 strains of flagellin proteins of Salmonella typhi isolates taken from Central Java (5 strains from Semarang, 1 strain from Salatiga, 1 strain from Magelang) and 2 isolate strains from Yogyakarta (1 strain from Doctor Sarjito Hospital, and 1 strain from Bethesda Hospital). Flagellin gene (fliC) amplification is conducted using PCR (primer LPW 1856 and LPW 1857). Flagellin proteins resulted from Alexan method (2009) is then modified while flagellin protein profiles are obtained with SDS-PAGE method. The results show that the size of flagellin gene (fliC) of S. typhi Isolates from Salatiga and the 8 other strains is respectively 1262bp and 1500bp. Flagellin proteins which are composed of 2-6 protein sub-units consist of 1-2 major proteins and 1-4 minor proteins with the sizes of 16-116 kDa.Keywords: Salmonella typhi, flagellin, Molecular Characterizations